Biomaterials in organoid development - Abdul Samat, Asmak; Yahaya, Badrul Hisham (Springer Nature, 2022)
Introduction: The animal model and the traditional two-dimensional (2D) cell culture have long been used to understand the biology and pathology of cell behaviour. However, neither technique captures precise cell behaviours, such as the in vivo cell-cell and cell-extracellular matrix (ECM) interactions and intra- and interorgan interactions. Organoids are three-dimensional cell culture systems known to simulate many of the structural and functional features of the organ. The microenvironment and signals within the body profoundly affect the development of stem cells in vitro and in vivo. Organoid culture matrices range from naturally derived to synthetic biomaterials with varying biophysical properties. This chapter focuses on the regulation of cell-matrix interactions that direct the decision of stem cells, including the various types of biomaterials used for the reproducible generation and control of organoid cultures. Methods: A few databases, such as Google Scholar, PubMed, and Scopus, were used to select literature with keywords organoids; extracellular matrix; cell interaction and regulation; biomaterials; natural and synthetic matrices. Results: Organoids provide a reliable tool for a wide range of disease modelling and a potential drug screening and toxicity testing strategy. However, it is difficult to control stem cell fate to promote proliferation and differentiation into specific cell types. The stem cell fate is determined by many factors, particularly the appropriate matrices required for multiple stages of organoid development and subsequent in vivo propagation. Conclusion: Organoids can be used to investigate human physiology in vitro, but their maturation depends on the stem cells’ capacity to form highly organised structures. Stem cell development and essential design parameters for organoid matrices are affected by various material features, including the presentation of cell-binding ligands, matrix dynamics, structural geometry, and degradability. Three-dimensional (3D) ECMs can be tailored to optimise the numerous structural and metabolic characteristics that influence cell fate.